Related-key impossible boomerang cryptanalysis on LBlock - Min XIE; Yan-li MU (Tongxin xuebao)
The related-key impossible boomerang cryptanalysis and the strength of the lightweight block cipher LBlock against this method were investigated.A new attack on 22-round LBlock was presented combining impossible boomerang attacks with related-key attacks.A 15-round related-key impossible boomerang distinguisher was constructed.Based on the new distinguisher,an attack on 22-round LBlock was mounted successfully by concatenating 3-round to the beginning and 4-round to the end.The attack on 22-round LBlock required data complexity of only 251.3plaintexts and computational complexity of about 2 71.5422-round encryptions.Compared with published cryptanalysis results on 22-round LBlock,proposed attack has great advantages on data and computational complexities.